2022
DOI: 10.31083/j.jin2101038
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of human umbilical cord mesenchymal stem cell on sepsis-associated encephalopathy in mice by regulating PI3K/AKT pathway

Abstract: Sepsis-associated encephalopathy is a common brain diseases, presenting severe di fuse brain dysfunction. The umbilical cord mesenchymal stem cells have been reported to have protective role for treating diseases, while its role in sepsis-associated encephalopathy remained elusive. This brief report investigated the therapeutic effect of umbilical cord mesenchymal stem cells on sepsis-associated encephalopathy in mice model and uncovering the underlying mechanism. The sepsis-associated encephalopathy mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Quantitation of FITC in brain tissue homogenates confirmed these findings showing a significant amount in the brains of Cntnap2 − / − rats than the control group and thus indicating a compromised BBB. Another well-accepted technique to determine BBB integrity is penetration of Evans blue dye into the brain [ 84 , 85 , 86 , 87 , 88 , 89 ]. On par with our FITC permeability data, we observed significantly high amounts of Evans blue dye in the brain homogenates of Cntnap2 − / − rats, whereas very low levels were detectable in the brain tissues of the control group suggesting impaired BBB permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitation of FITC in brain tissue homogenates confirmed these findings showing a significant amount in the brains of Cntnap2 − / − rats than the control group and thus indicating a compromised BBB. Another well-accepted technique to determine BBB integrity is penetration of Evans blue dye into the brain [ 84 , 85 , 86 , 87 , 88 , 89 ]. On par with our FITC permeability data, we observed significantly high amounts of Evans blue dye in the brain homogenates of Cntnap2 − / − rats, whereas very low levels were detectable in the brain tissues of the control group suggesting impaired BBB permeability.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the injection of umbilical cord MSCs (UC-MSCs) via femoral vein significantly reduced the expression levels of TNF-α, IL-6 and HMGB1 as well as microglia activation (expression of Iba-1 markers) in brain tissue of LPS-treated mice. This improved cortical neuronal damage and cognitive impairment ( Zhang Z. et al, 2022 ). Some studies suggested that MSCs can migrate into the brain through paracellular or transcellular pathways ( Schmidt et al, 2006 ).…”
Section: Interaction Between Brain and Peripheral Neuroimmune System ...mentioning
confidence: 99%